An Expiremental Investigation on Cable Reinforcement - Aziz NI; Hii J; Fabjanczyk MW (The Australasian Institute of Mining and Metallurgy, 1986)
The paper presents the results of a series of pull out tests performed on roof reinforcement systems currently being adopted in mines in Australia 7mm wire, dividag bar, 15.2mm strand cable, and birdcage cable. The study also investigated the load deformation chara- cteristics and the various design parameters controlling the effectiveness of a cable-grout system. Suggestions for continued work are Highlighted.